Implementasi Budaya Sunda: Program Melestarikan Budaya Sunda di SDN Cigereleng - Isma Samrotul Fuadah; Yuni Hamidah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research intends to explore Sundanese culture which is still preserved in a public elementary school in Cigereleng. The background of this research is to look at the daily activities of Sundanese culture carried out by students in preserving Sundanese cultural values, because with the development of a more modern era so that most students do not pay attention to Sundanese culture, the school applies Sundanese cultural values in every learning activity and also skills at SDN Cigereleng school. We collected data using observation and interview techniques with a resource person, namely the homeroom teacher of grade 6. To provide information related to this research data, we visited the Cigereleng Elementary School to collect data and students' work. The results of the study show that Sundanese cultural values in schools have begun to be implemented and have been running from 1999 to 2023 and have developed because there are new teachers who are competent in Sundanese culture.